Children's and Adolescents' Evaluations of Intergroup Exclusion in Interracial and Interwealth Peer Contexts. Issue 2 (29th May 2019) - Burkholder, Amanda R.; Elenbaas, Laura; Killen, Melanie
Abstract : Children and adolescents ( N = 153, ages 8–14 years, M age = 11.46 years) predicted and evaluated peer exclusion in interwealth (high‐wealth and low‐wealth) and interracial (African American and European American) contexts. With age, participants increasingly expected high‐wealth groups to be more exclusive than low‐wealth groups, regardless of their depicted race. Furthermore, children evaluated interwealth exclusion less negatively than interracial exclusion, and children who identified as higher in wealth evaluated interwealth exclusion less negatively than did children who identified as lower in wealth. Children cited explicit negative stereotypes about high‐wealth groups in their justifications, while rarely citing stereotypes about low‐wealth groups or racial groups. Results revealed that both race and wealth are important factors that children consider when evaluating peer exclusion.